Large-scale transfer-free growth of thin graphite films at low temperature for solid diffusion barriers. Issue 31 (25th July 2018) - Kang, Su Hyoung; Kang, Sangmin; Park, Seong Chae; Park, Jong Bo; Jung, Youngjin; Hong, Byung Hee
Abstract : Amorphous indium–gallium–zinc oxide (a-IGZO) thin-film transistors (TFTs) have been under intense investigation as one of the promising candidates for active matrix flat-panel displays. Abstract : Amorphous indium–gallium–zinc oxide (a-IGZO) thin-film transistors (TFTs) have been under intense investigation as one of the promising candidates for active matrix flat-panel displays. However, solid diffusion of a-IGZO to other layers during TFT device fabrication highly degrades their electrical and optical properties. It is expected that the diffusion-impenetrable properties of graphitic materials can be utilized as diffusion barriers. A conventional transfer method and direct growth on TFTs with high temperature are limited due to wet transfer conditions and low T g (∼540 °C) of the glass substrates, respectively. Here we report the large-scale transfer-free growth of thin graphite films at low temperature (∼350 °C) for solid diffusion barriers in the a-IGZO TFTs using plasma enhanced chemical vapor deposition (PECVD), which can be widely used to protect solid-diffusion for sustainable and scalable future industrial technology.